Existence of positive weak solutions for stationary fractional Laplacian problem by using sub-super solutions - Guefaifia R.; Boulaaras S.; Jan R. (Walter de Gruyter GmbH, 2025)
In this work, we establish a theorem concerning the extension of positive weak solutions for a stationary fractional Laplacian problem featuring weight functions that change sign. Additionally, we introduce novel conditions to ensure the existence of a positive solution for the given problem. These conditions are derived utilizing the approach of sub-super solutions, thereby extending and complementing existing results in the literature. ? 2024 Walter de Gruyter GmbH, Berlin/Boston.